If it's not what You are looking for type in the equation solver your own equation and let us solve it.
h+3.13/2=3*3.14/2
We move all terms to the left:
h+3.13/2-(3*3.14/2)=0
We add all the numbers together, and all the variables
h+3.13/2-(+3*3.14/2)=0
We get rid of parentheses
h+3.13/2-3*3.14/2=0
We multiply all the terms by the denominator
h*2+3.13-3*3.14=0
We add all the numbers together, and all the variables
h*2-6.29=0
Wy multiply elements
2h-6.29=0
We move all terms containing h to the left, all other terms to the right
2h=6.29
h=6.29/2
h=3+0.29/2
| 1y-3(2y-7)=76 | | 3.50r+2r+7-2=5 | | 5-2x=-1-3x | | -4(-2x+3)=-52 | | -4x+12=-4-4x+12=-4 | | 3m2+m=30 | | 2r+19=20 | | 4x-(-x-5)=20 | | 45+5/6x=60 | | 3x-30=2-x | | .1t^2+3t=400 | | F(x)=-5/2x+4= | | 6(x+5)=-6x+42 | | -16-2x=-4x+14 | | V=43πr3 | | 26-4x= | | 27-3x=3x+27 | | 3(2f+4)=20(3f-6) | | -3x+2=-3 | | (8x-3)-(4x-7)=20 | | -(p+4)+40p2= | | 20s+20=-15s | | 9T+T-5T=6x5 | | 4x-12/5x-15=4/5 | | H=38+16t-16^2 | | 27-3x=3+27 | | 1.73=3^x | | X+(1/2×x)+(3+x)=86 | | 4/13r=6.5 | | 5(x+6)+(-3)=37 | | 1.331=c^2 | | 7x(8)=4 |